Indonesia's Foreign Policy: Grasping the Public's Perspective on the War in Ukraine - Pamungkas, Raka (Journal of International and Local Studies, 2024)
This research emphasizes the importance of public opinion for Indonesia’s foreign policy in the context of the Russia-Ukraine war. As a middle-power democracy, Indonesia should recognize public opinion as a crucial component in formulating its foreign policy toward the war. On this note, Indonesian public opinion remains influenced by anti-Western sentiments, leading to empathy towards Russia and President Vladimir Putin. Meanwhile, Indonesia’s voting position at the 11th Emergency Special Session of the United Nations General Assembly (UNGA) related to the Russia-Ukraine war did not align with this public opinion. The Government of Indonesia based its stance on full respect for Ukraine’s sovereignty and concerns about the humanitarian consequences on civilians. Nevertheless, Indonesia refrained from supporting economic sanctions against Russia and continued to invite President Vladimir Putin to the G20 Summit in 2022. In this regard, Indonesia employs a “pragmatic equidistant” foreign policy towards Russia and Ukraine, aiming to maximize partnerships based on national interests without being drawn into any sphere of influence. While public opinion should not be the sole determinant in Indonesia’s foreign policymaking, it remains significant to ensure the legitimacy of the democratic process. Therefore, after looking at the benefits and challenges of three policy choices, this policy paper strongly recommends establishing a partnership with reputable Public Opinion research institutions in Indonesia. This is the most feasible and practical option for the MoFA’s medium- and long-term strategies to assert Indonesia’s stance as a middle-power democracy.